Direct (hetero)arylation (DHAP) polymerization of conjugated polymers - new A-B-A monomer design for P(NDI2OD-T2) & the challenges of adopting DHAP for continuous flow processes - Kakde, Navnath R.; Bharathkumar, H. J.; Wavhal, Bhaiyyasaheb A.; Nikam, Arun; Patil, Suneha; Dash, Soumya Ranjan; Vanka, Kumar; Krishnamoorthy, K.; Kulkarni, Amol; Asha, S. K. (Journal of Materials Chemistry C, 2022)
P(NDI2OD-T2), also known as Polyera ActivInk N2200, was synthesized by the atom-economic direct hetero arylation polymerization (DHAP) route using a newly designed A-B-A monomer. The new monomer design involved flanking naphthalene diimide with bithiophene units in the bay position, which was further polymerized with bay substituted 1,4-dibromo naphthalene diimide, to afford the same polymer structure as P(NDI2OD-T2). The new monomer design resulted in a very high molecular weight (M-n: 99.5 kDa, D-M: 2.8) defect-free polymer in a quantitative yield by the DHAP batch process using 1,2,4-trichlorobenzene (TCB) as the solvent. DFT studies revealed that the abstraction of the alpha-proton from the naphthalene diimide substituted 2,2 `-bithiophene was favorable by 2.6 kcal mol(-1) (Delta Delta G) as compared to that from 2,2 `-bithiophene. The reason for this improved C-H activation at the alpha position can be attributed to the presence of C-HMIDLINE HORIZONTAL ELLIPSIS pi stabilizing interactions in naphthalene diimide substituted 2,2 `-bithiophene, which strengthens upon the extended charge delocalization throughout the ring, thus stabilizing the conjugate base generated after the proton abstraction. Continuous flow polymerization was carried out by pumping the DHAP reaction mixture including the monomers, catalyst, and additive (pivalic acid) solubilized in degassed TCB through a pre-heated glass condenser packed with K2CO3 and Celite under aerobic conditions. Reproducible molecular weights of M-n: 29.5 kDa, D-M: 1.7 were obtained at much lower concentrations of reactant mixture compared to that for batch polymerization. This is the first report of the synthesis of P(NDI2OD-T2) by a Continuous Flow Process adopting the DHAP route to obtain a defect-free polymer with reasonable molecular weights. P(NDI2OD-T2) was also synthesized by Stille polymerization as a reference control sample to compare the thermal and charge carrier transport properties of the DHAP polymers. Organic field-effect (OFET) mobility measurements indicated mobility values in the order of 10(-3) cm(2) V-1 s(-1) for the DHAP batch polymer (using the novel monomer design). The P(NDI2OD-T2) synthesized by DHAP batch using the commonly used starting materials - bisbromo naphthalene diimide and bithiophene, exhibited OFET mobilities which were one order less, similar to 10(-4) cm(2) V-1 s(-1). This observation highlights the importance of structural design in the monomer to enhance reactivity and thereby the bulk properties using the DHAP route.

Exploring SiliaCat Pd-DPP as a recyclable heterogeneous catalyst for the multi-batch direct heteroarylation polymerization for P(NDI2OD-T2) - Kakde, Navnath R.; Asha, S. K. (Polymer Chemistry, 2023)
Donor-acceptor (D-A) conjugated polymers like P(NDI2OD-T2) are important constituents of the active layer of energy conversion devices like all-polymer solar cells. A cost-effective and environmentally amiable pathway for the synthesis of this and similar D-A polymers is highly desirable for the large-scale production of these materials. In this report we have combined two cost-effective approaches, namely, direct heteroarylation polymerization (DHAP) and a recyclable heterogeneous catalyst (SiliaCat Pd-DPP), for the multi-batch synthesis of P(NDI2OD-T2). The general applicability of the approach was first established with a series of conjugated small molecules based on naphthalene diimide and bithiophene derivatives (N1 to N6). The Meitlis hot filtration test and inductively coupled plasma-optical emission spectroscopy (ICP-OES) were conducted to estimate the quantity of leached palladium in the final reaction product. Catalyst recyclability up to five cycles was demonstrated for N1 with <2 ppm leached palladium impurity. A comparison was made with the homogeneous catalyst Pd(2)dba(3) which indicated the presence of much higher levels of palladium impurity in the final product. The polymerization of P(NDI2OD-T2) was demonstrated using the regular monomers (NDIOD-Br-2 and bithiophene) and also using a modified monomer with activated bithiophene (naphthalene diimide substituted bithiophene) under DHAP conditions employing SiliaCat Pd-DPP as the recyclable heterogeneous catalyst. The modified monomer proved to be amenable to DHAP polymerization using SiliaCat Pd-DPP as the heterogeneous catalyst, which could be consecutively reused four times with reproducible molecular weights in the range of M-n/M-w: 27.1/49.0 to 33.5/61.3.

High-voltage symmetric supercapacitor electrodes via in situ synthesized multiwalled carbon nanotube-doped perylenebisimide-based donor-acceptor conjugate polymer P(PDI2OD-T2) - Wavhal, Aryan Anurath; Dilwale, Swati; Puthiyaveetil, Priyanka Pandinhare; Kakde, Navnath R.; Prakash, Medha; Kurungot, Sreekumar; Asha, S. K. (Journal of Physical Chemistry C, 2024)
This study presents the design and synthesis of a donor-acceptor pi-conjugated polymer composite P(PDI2OD-T2)/MWCNT tailored for high-voltage symmetric supercapacitor applications. The synthesis of P(PDI2OD-T2)/MWCNT was expedited by adopting a novel in situ polymerization technique that modifies the traditional Stille polymerization process. Incorporating approximately 33% by weight of multiwalled carbon nanotubes (MWCNT) into the polymer matrix, referred to as P-2, significantly enhances its conductivity, surface area, and porosity. These improvements in the material properties contribute to the superior electrochemical performance of the composites by promoting efficient electrolyte ion transport across the electrode-electrolyte interfaces. The symmetric supercapacitor devices fabricated with P-2 electrodes employing both liquid organic (LE-P-2||P-2) and quasi-solid-state gel (QSS- P-2||P-2) electrolytes demonstrate capacitance values of 85.4 and 84.2 F g(-1), respectively, at a current density of 0.25 A g(-1), while operating at a high-voltage window of 3.1 V. Moreover, these devices exhibit robust cycling stability, maintaining approximately 70% of their initial capacitance over 45,000 cycles with a coulombic efficiency of 96%. The successful demonstration of a quasi-solid-state symmetric supercapacitor underscores the potential of flexible energy storage solutions, as evidenced by a PMMA LiClO4 gel electrolyte prototype. This flexible device not only maintains structural integrity but also achieves an impressive power density of 18,600 W kg(-1) and an energy density of 112.4 Wh kg(-1), indicating its practical viability for real-world applications.

Rational monomer design for the synthesis of conjugated polymers by direct heteroarylation polymerization - Kakde, Navnath R.; Sharma, Himanshu; Dalvi, Nitin V.; Vanka, Kumar; Asha, S. K (ACS Polymers Au, 2024)
This study focuses on the design concepts that contribute to the C–H activation in bithiophene-flanked monomers incorporating naphthalene diimide (NDI), perylene diimide (PDI), and fluorene (FLU) and their polymerization by direct heteroarylation. Density functional theory (DFT) calculations reveal distinct energy requirements for C–H bond abstraction, which is dictated by the electron-withdrawing strength of the central aromatic core flanked by bithiophene. These provide insights into the reactivity of each monomer for C–H bond activation. Proton NMR spectroscopic experimental results confirm the favorable energetic profiles predicted by DFT, with NDI- and PDI-flanked monomers exhibiting lower energy requirements than fluorene-flanked monomers. Successful polymer synthesis is demonstrated for NDI and PDI, while the fluorene-flanked monomer shows challenges due to its higher energy demands.